Sexuality and relationship education for children and adolescents with autism spectrum disorders : a professional's guide to understanding, preventing issues, supporting sexuality and responding to inappropriate behaviours - Hartman, Davida (Jessica Kingsley Publishers, 2014)
Children and adolescents with Autism Spectrum Disorders (ASD) require specialized teaching strategies when learning about the body, sexuality, and relationships. This complete sex education resource provides practical teaching advice, activity ideas, and illustrated handouts geared towards the needs of children of all ages on the autism spectrum.